(untitled) - Webber, Jeremy H. A. (Oxford, 2015)
The book introduces and describes the principal characteristics of the Canadian Constitution, including Canada's institutional structure and the principal drivers of Canadian constitutional development.
Keywords: Constitutional law,Luật hiến pháp; Canada,Canada